Clinical characteristics and prognosis of non-typhoidal Salmonella bacteremia in children vs. adults: a retrospective study - Jianwei Su; Wanping Zhong; Baofang Liang; Yanhong Wang (Frontiers in Medicine)
BackgroundSeveral studies have reported the clinical characteristics of non-typhoidal Salmonella (NTS) bacteremia in children and adults. However, there is a lack of data that directly compares the clinical characteristics and prognosis in children vs. adults.MethodsA retrospective study was conducted on bloodstream infections caused by NTS in hospitalized patients from 1 January 2018 to 31 December 2024. The clinical and relevant laboratory data of patients between adult and pediatric groups were compared, and the risk factors predicting the duration of antibiotic treatment were analyzed by multivariate logistic regression.ResultsIn total, 52 patients with NTS bloodstream infection met the eligibility criteria, with 28 (53.8%) being children vs. 24 (46.2%) adults. Respiratory infections are the most concomitant diseases (children 78.6% vs. adults 50.0%, p = 0.031). More than half of pediatric patients isolated NTS from their stool (children 57.1% vs. adults 20.8%, p = 0.008). The duration of antibiotic treatment in children is significantly lower than that in adults {8 children (6.5, 10.5) vs. 15 adults (7.25, 21.25), p = 0.002}; however there is no significant difference in mortality rates. Multivariate logistic regression analysis showed that children (OR = 0.209, 95% CI: 0.058 ~ 0.751, p = 0.016) had a shorter course of antibiotic treatment.ConclusionA shorter course of antibiotic treatment was observed in pediatric patients; however, due to its biases and limitations, further prospective randomized controlled trials are needed to generalize our findings.